The Effect of Employee Adaptation to STARA (Smart Technology, Artificial Intelligence, Robotics and Algorithm) with Service Performance Mediated by Job Crafting, Job Insecurity, and Work Engagement - Afni Felina Adya; Putri Mega Desiana (Green Publisher Indonesia, 2025)
This research investigates the impact of employee adaptation to STARA (Smart Technology, Artificial Intelligence, Robotics, and Algorithm) on service performance, considering the mediating roles of job crafting, job insecurity, and work engagement. Employing an explanatory quantitative approach with Structural Equation Modeling (SEM), data were collected from 249 frontline employees in Jabodetabek who interact with customers and utilize STARA in their work. The results reveal that STARA awareness as a challenge appraisal positively influences service performance, whereas hindrance appraisal has a negative effect. Work engagement and job crafting significantly mediate the positive relationship between challenge appraisal and service performance, while job insecurity exacerbates the negative impact of hindrance appraisal. The study offers theoretical contributions by clarifying adaptive mechanisms to STARA in the service sector. Practically, it suggests organizations enhance training and psychological support to boost work engagement, implement job crafting programs to reduce job insecurity, and adopt clear communication strategies to position STARA as an opportunity rather than a threat.